Precarious mobility and spectacle dwelling on a ferry commute. Issue 1 (2nd January 2020) - Roseman, Sharon R.
ABSTRACT: Precarious mobilities caused by insufficient capacity or unplanned stoppages of public transportation services can result in line-ups that are as much a part of commuters' daily routines as travel itself. This article explores how excessive line-ups can be analyzed as forms of spectacle dwelling in the context of a Canadian aquamobile transportation corridor on Conception Bay, linking Bell Island to the main island of Newfoundland. For several decades, Bell Island ferry commuters have been governed by vivid representations of the bureaucracy literally seizing up in users' stalled movement for hours or sometimes days. Based on an application of concepts initiated by Debord, this article discusses how such line-ups comprise forms of spectacle dwelling; the role of commentaries about these spectacles; and examples of counter-spectacles in 2017 that created a forum for protesting changes to the service.